The moderator role of emotion regulation ability in the link between stress and well-being - Extremera, Natalio; Rey, Lourdes (Frontiers in Psychology, 2015)
This article examined the moderating role of a central core dimension of emotional intelligence – emotion-regulation ability – in the relationship between perceived stress and indicators of well-being (depression and subjective happiness) in a sample from a community adult population. The relationships for males and females on these dimensions were also compared. Results revealed that emotion-regulation abilities moderated both the association between perceived stress and depression/happiness for the total sample. However, a gender-specific analysis showed that the moderation effect was only significant for males. In short, when males reported a high level of perceived stress, those with high scores in regulating emotions reported higher scores in subjective happiness and lower depression symptoms than those with low regulating emotions. However, no interaction effect of regulating emotions and stress for predicting subjective happiness and depression was found for females. In developing stress management programmes for reducing depression and increasing well-being, these findings suggest that training in emotional regulation may be more beneficial for males than females. Our findings are discussed in terms of the need for future research to understand the different gender associations and to consider these differences in further intervention programmes.